2021
DOI: 10.21608/edj.2020.47230.1303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an in-Office Bleaching Agent Containing Two Different Concentrations of Titanium Dioxide Nano Particles on the Color and Surface Roughness of Enamel.

Abstract: Background: The aim of this study was to evaluate the effect of two different concentrations of titanium dioxide nano particles TiO 2 NP on the color and surface roughness of enamel surface. Material and methods: 20 bovine anterior teeth were selected. Each tooth was divided into two equal halves and distributed to two groups A and B. Group A: one half is subjected to bleaching agent (AI) and the other half to bleaching agent mixed with 5% TiO 2 NP (AII). Group B: one half is subjected to bleaching agent (BI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Hamza and colleagues investigated TiO 2 NPs as a teeth-whitening agent in two different concentrations (5 % and 10 % TiO 2 ). The final result showed that the amount of TiO 2 nanoparticle in the formulation had no effect on whitening, and the two formulations had similar effects [ 178 ]. To improve the efficiency of TiO 2 as a bleach, Bulavinets and co-workers prepared Ag–TiO 2 NPs.…”
Section: Nanomaterialsmentioning
confidence: 99%
“…Hamza and colleagues investigated TiO 2 NPs as a teeth-whitening agent in two different concentrations (5 % and 10 % TiO 2 ). The final result showed that the amount of TiO 2 nanoparticle in the formulation had no effect on whitening, and the two formulations had similar effects [ 178 ]. To improve the efficiency of TiO 2 as a bleach, Bulavinets and co-workers prepared Ag–TiO 2 NPs.…”
Section: Nanomaterialsmentioning
confidence: 99%